Nutrient Composition of African Breadfruit (Treculia africana) Seed Hull and its Use in Diets for the African Giant Land Snail, Archachatina marginata - Ejidike, B.N.; Ajileye, O. (Pakistan Journal of Nutrition, 2007)
A feeding trial was conducted to evaluate the use of Treculia africana seed hull meal (TASHM) as replacement for maize in diets for the African giant land snail, Archachatina marginata. Seeds of T. africana were parboiled, dehulled, milled and used to replace maize at 0 percent, 15 percent, 30 percent and 45 percent (diets I, II, III and IV, respectively) in isoproteic diets (20 percent crude protein). Juvenile A. marginata (n = 36; 30±1.5 g) were randomly grouped into three snails per group for the three replicates of each diet treatment and stocked in cages. The diets were fed to snails once daily at 2 percent body weight per day for 70 days. Performance of snails was based on body weight gain, shell length, shell width, shell aperture increase and survival. No mortality was recorded. Mean body weight gain of the snails fed diet III was highly influenced (p0.05) while the mean body weight gain of snails fed diet I had significant difference (p0.05) existed between the feed conversion ratio of the snails on the diets. The effect of the diets on the morphological parameters of snails did not differ significantly (p>0.05).